PmSN15218: A Potential New Powdery Mildew Resistance Gene on Wheat Chromosome 2AL - Sun, Meng; Liu, Qi; Han, Yi; Liu, Guojun; Wu, Jiajie; Qi, Juan; Ni, Fei; Bao, Yinguang (Frontiers in Plant Science, 2022)
Powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is a devastating fungal disease that seriously damages the yield and quality of wheat in many regions of the world. Identifying new resistance genes and breeding new resistant varieties are effective methods to control this disease. The breeding line SN15218 shows good resistance against powdery mildew. We therefore developed an F2 population and 287 F2:3 families crossed between SN15218 and the powdery mildew susceptible cultivar HuiXianHong (HXH). Genetic analysis indicated that a single dominant gene, designated herein PmSN15218, conferred resistance to the Bgt isolate E09 in SN15218. Bulked segregant RNA-Seq (BSR-Seq) analysis revealed that PmSN15218 is located in a ~25-Mb interval on chromosome 2AL. Using the polymorphism information between SN15218 and HXH, we developed twelve PCR markers and mapped this gene to a 0.5-cM genetic interval between the two flanking markers PmM12 and PmM14, corresponding to a 6.01-Mb physical region in the Chinese Spring reference genome. The results of molecular marker analysis, allelic tests of resistance spectrum and DNA resequencing indicated that PmSN15218 is distinct form the known resistance gene Pm4b on 2AL.